2004
DOI: 10.1074/jbc.m401372200
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin-induced Migration Requires Signaling through Protease-activated Receptor 1 and Integrin α9β1

Abstract: Plasmin is a major extracellular protease that elicits intracellular signals to mediate platelet aggregation, chemotaxis of peripheral blood monocytes, and release of arachidonate and leukotriene from several cell types in a G protein-dependent manner. Angiostatin, a fragment of plasmin(ogen), is a ligand and an antagonist for integrin ␣ 9 ␤ 1 . Here we report that plasmin specifically interacts with ␣ 9 ␤ 1 and that plasmin induces migration of cells expressing recombinant ␣ 9 ␤ 1 (␣ 9 -Chinese hamster ovary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 49 publications
0
67
0
1
Order By: Relevance
“…The ␣9␤1 integrin has now been described to interact with a relatively large number of ligands including tenascin C, osteopontin, vascular cell adhesion molecule-1, coagulation factor XIII, and several members of the ADAMs family of transmembrane metalloproteinases (7,24,(45)(46)(47). The biological significance of ␣9␤1 interactions with most of these ligands remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The ␣9␤1 integrin has now been described to interact with a relatively large number of ligands including tenascin C, osteopontin, vascular cell adhesion molecule-1, coagulation factor XIII, and several members of the ADAMs family of transmembrane metalloproteinases (7,24,(45)(46)(47). The biological significance of ␣9␤1 interactions with most of these ligands remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibitors of JAK, p38 MAPK, and NF-B revealed that these signaling pathways are indispensable for the plasmin-mediated tumor necrosis factor-␣ and IL-6 induction in the cells. In addition, angiostatin, a fragment of plasmin(ogen), is a ligand and an antagonist for integrin ␣9␤1 (27). Angiostatin, representing the kringle domains of plasmin, alone did not induce the migration of Chinese hamster ovary (CHO) cells, but simultaneous activation of the G protein-coupled protease-activated receptor-1 with an agonist peptide induced the migration on angiostatin.…”
Section: Discussionmentioning
confidence: 99%
“…1D, 1F) with U0126, an MEK/ERK inhibitor, abolished the Pla-induced migration. Although Pla is a known in vitro inducer of cell migration of both cells types used in the present study, fibroblasts (22), and monocytes/macrophages (17, 31), we applied a different migration assay to validate the data obtained from the scratch assay, because it could be difficult to differentiate between migration and proliferation. By using a chemotaxis assay we were also able to observe that U0126 efficiently decreased macrophage migration (Fig.…”
Section: Pla-induced In Vitro Cell Migration Is Dependent On Mek/erk mentioning
confidence: 99%
“…Some of these effects are followed by the activation of the transcription factors NF-kB and AP-1 (16)(17)(18)(19). Pla also triggers multiple signaling pathways such as JAK/STAT, p38 MAPK, and ERK1/2 (18)(19)(20) and it has been shown to activate protease-activated receptor-1 (PAR-1) in fibroblasts (21,22). We have previously demonstrated that the proinflammatory cytokine IFN-a increased the expression of the Plg receptor a-enolase on the surface of human monocytes with a consequent increase of Pla generation and proteolysis (23).…”
mentioning
confidence: 99%